The influence of atmospheric circulation on bioclimatic conditions in Lublin (Poland) - Bartoszek, Krzysztof; Wereski, Sylwester; Krzyżewska, Agnieszka; Dobek, Mateusz (Bulletin of Geography. Physical Geography Series, 2017)
This study provides evaluation of the relationship between atmospheric circulation conditions and the frequency of heat/cold stress incidence in Lublin in the years 1951-2010 according to the Universal Thermal Climate Index (UTCI). The paper outlines the frequency and conditional probability of heat/cold stress occurrence during particular circulation types and the analysis of the circulation patterns that induce these incidents. The increased wind velocity had a significant effect on forming unfavorable bioclimatic conditions in the winter. Whereas, in summer, heat stress was observed nearly exclusively when high pressure system from the eastern part of Europe induces a slow inflow of very warm air masses from the eastern or southern directions.